DAMPAK PENDAMPINGAN ORANG TUA PADA PERKEMBANGAN SOSIAL ANAK USIA DINI DI TK NEGERI 01 SUNGAI RUMBAI - Sunimaryanti, Sunimaryanti; Sari, Ayu Mustika; Sari, Defita Sari; Antika, Mira; Rahmah, Sunia (Dharmas Education Journal (DE_Journal), 2024)
This research aims to examine the influence of parental support on the social development of early childhood at TK Negeri 01 Sungai Rumbai. Parental support is an important factor in developing children's social skills, such as interacting with peers, recognizing emotions, and resolving conflicts. Using descriptive qualitative methods, data was collected through observations of teachers at school and at home, interviews regarding parental assistance, and documentation with participants in the form of 25 parents, 3 teachers, and the school principal. The theory used was Erikson's theory of social development, involvement Epstein's parents, and Bandura's social learning theory. The research results show that intensive parental assistance has a positive impact on children's social interaction, adaptation and cooperation abilities in the school environment. Children who are actively accompanied by their parents have more developed social skills than children who receive less assistance. These findings reinforce the importance of parental involvement in early childhood education to support children's social development. Children who receive substantial help from parents show superior social skills compared to children who receive minimal support. These results show the important role of parents in actively helping young children to ensure optimal social growth with the highest score of 4.2 and a success rate of 84%